1990
DOI: 10.3168/jds.s0022-0302(90)79002-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Changes in Condition Score to Cow Health in Holsteins

Abstract: The relationship of body condition score with disease occurrence was examined in 561 cows in nine herds. Cows were body condition scored on a five-point scale (1 = thin, 5 = obese) every 2 wk from drying off until 150 d in milk. Cows scored between 3- and 3+ were considered to be in average or good condition. Cows scored less than or equal to 2+ were considered to be underconditioned, whereas those scored greater than or equal to 4- were considered to be overconditioned. Relationships of health and condition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
3
33

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 20 publications
12
139
3
33
Order By: Relevance
“…Adamski (1) recorded a significant positive correlation between BCS on the calving day and dystocia, particularly in primiparous cows. Moreover, Gearhart et al (12) showed an increased risk of dystocia in cows with a deteriorating body condition during the dry period. Nogalski (21) presented a negative effect of too weak condition (<3.0 BCS), while Borkowska and Januś (5) -too fat BCS (>3.5) at calving as the main cause for dystocia.…”
Section: Discussionmentioning
confidence: 99%
“…Adamski (1) recorded a significant positive correlation between BCS on the calving day and dystocia, particularly in primiparous cows. Moreover, Gearhart et al (12) showed an increased risk of dystocia in cows with a deteriorating body condition during the dry period. Nogalski (21) presented a negative effect of too weak condition (<3.0 BCS), while Borkowska and Januś (5) -too fat BCS (>3.5) at calving as the main cause for dystocia.…”
Section: Discussionmentioning
confidence: 99%
“…This means that high BCS during the dry period, results on average in a more severe and probably also longer lasting cNEB in these cows and should therefore regarded as risk factor for non adaptation. Monitoring BCS can also be used to calculate BCS loss during lactation [32,42]. A characteristic of this easy applicable method is that the outcome of this method may differ between observers.…”
Section: Negative Energy Balance and Adaptation: Definition Quantifimentioning
confidence: 99%
“…Butler and Smith [16] found that days from calving to ovulation increased by 0.7 for each extra MJ energy being mobilised from body per day. Similarly, associations have been shown between body condition loss in early lactation and health problems [45,100]. Given the link between body fatness at calving and subsequent degree of mobilisation, it is clearly important to manage cows to calve at the optimum body fatness.…”
Section: Body Fatmentioning
confidence: 99%
“…Fatty liver, ketosis and a multitude of other metabolic disorders in the post-partum cow are all predisposed by excessive mobilisation of body reserves [29,45,51,67]. Reproductive performance is also impaired by excessive lipid mobilisation [16,37].…”
Section: Strategies To Prime For Body Mobilisationmentioning
confidence: 99%